2019
DOI: 10.1177/000313481908501230
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Therapeutic Benefit of Bupivacaine HCl Transversus Abdominis Plane (TAP) Block as Part of an Enhanced Recovery Pathway versus Traditional Oral and Intravenous Pain Control after Minimally Invasive Colorectal Surgery: A Prospective, Randomized, Double-Blind Trial

Abstract: Enhanced recovery pathways (ERPs), when combined with transversus abdominis plane (TAP) blocks, have been proven to reduce the length of stay (LOS) and improve quality outcomes. Nonopioid pain management is an essential component of this pathway, leading to a reduction in immobility, postoperative ileus, and an increase in patient satisfaction. TAP block variations have been studied in general and gynecologic surgery. This study evaluates the effectiveness of laparoscopic TAP blocks in conjunction with the ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…As this technique is relatively new and was first introduced in 2001 [64], data regarding POI are sparse. There are results demonstrating reduced length of stay and opioid consumption as well as improved bowel function compared to traditional regimes after MIS [32]. Not many studies have compared TAP block to epidural catheters.…”
Section: Transverse Abdominis Plane (Tap) Blockmentioning
confidence: 99%
“…As this technique is relatively new and was first introduced in 2001 [64], data regarding POI are sparse. There are results demonstrating reduced length of stay and opioid consumption as well as improved bowel function compared to traditional regimes after MIS [32]. Not many studies have compared TAP block to epidural catheters.…”
Section: Transverse Abdominis Plane (Tap) Blockmentioning
confidence: 99%
“…In the above equation, uq(•) refers to the sampling operation in the previous step, and the gradient of the given feature graph was calculated. After the calculation of the weight was completed, according to bias gradient equation (6) in the BP algorithm, the bias gradient of each feature map in layer l was calculated.…”
Section: Mr Imaging Technology Based On Deep Learningmentioning
confidence: 99%
“…erefore, it is very important to construct the surgical plane of the intestinal fascial space before surgery. e tumor and its mesangial membrane can be completely removed by following this surgical plane, and the adjacent organs, blood vessels, and autonomic nerve plexus in the pelvic cavity can be avoided as much as possible [6]. Shinohara et al [7] studied and analyzed embryological and anatomical theories similar to TME in 2009 and published the concept and technique of complete mesocolic excision (CME).…”
Section: Introductionmentioning
confidence: 99%
“…TAP block improves postoperative pain in several abdominal surgeries, including colectomy, nephrectomy, hysterectomy, cholecystectomy, and hernia repair [8,11,[13][14][15]. Damadi and colleagues [16] reported that the combined use of TAP block and the ERAS pathway reduced the use of postoperative narcotics, time to ambulation and bowel function, and hospital stay length in laparoscopic colorectal surgeries. However, various TAP block protocols (with varying local anesthetic volume and concentration, as well as adjuvant agent use), approach methods (lateral, posterior, or subcostal), injection times, continuous infusion uses, and surgery types have varying effects [8,14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Damadi and colleagues [16] reported that the combined use of TAP block and the ERAS pathway reduced the use of postoperative narcotics, time to ambulation and bowel function, and hospital stay length in laparoscopic colorectal surgeries. However, various TAP block protocols (with varying local anesthetic volume and concentration, as well as adjuvant agent use), approach methods (lateral, posterior, or subcostal), injection times, continuous infusion uses, and surgery types have varying effects [8,14,16,17]. TAP block has been reported to predominantly and acutely inhibit somatic pain [18,19].…”
Section: Introductionmentioning
confidence: 99%